Predicting future trends in the burden of pertussis in the 21st century: implications for infant pertussis and the success of maternal immunization. (2nd January 2016) - van den Biggelaar, Anita H J; Poolman, Jan T
Abstract : Support is growing for maternal immunization using acellular pertussis (aP) vaccines to prevent severe pertussis disease and deaths among very young, unvaccinated infants. Vaccine effectiveness of maternal immunization is 91% in preventing laboratory-confirmed pertussis in infants aged <3 months. To date, most mothers were primed in childhood with whole-cell pertussis vaccines. Soon, the generation of aP-primed individuals will become the new mothers-to-be. The shorter duration of protection afforded by aP vaccines, which is more pronounced with repeated aP boosters, may lead to increased pertussis circulation among aP-primed parents. Maternal Tdap immunization in aP-primed mothers-to-be may become less effective. Additional measures to protect young infants may eventually be needed, along with new vaccines that induce higher quality and more durable responses.